Resistance on the rise: Assessment of antibiotic-resistant indicator organisms in Shem Creek, Charleston, South Carolina - Brooke Emery; Heather Fullerton; Brian Bossak (Elsevier, 2022)
Shem Creek is a Charleston waterway well-known for numerous recreational activities such as paddle boarding, fishing, and kayaking. However, Charleston WaterKeepers, a local organization, has consistently found high levels of coliform bacteria within Shem Creek. With antibiotic prescription rates surging and coastal flooding becoming an increasing concern, antibiotic resistant bacteria (ARBs) have become both a public health and environmental risk. ARBs can lead to the spread of antibiotic-resistant infections (ARIs) within populations. Precipitation influences bacterial concentrations in a body of water. Immediately after rainfall, the levels of bacteria rise tremendously. Runoff from livestock, sewage, and hospitals are known to contribute to the development of ARBs in bodies of water. Consistent water testing is essential to preventing the risk and spread of ARIs and determining what additional factors contribute to the development of ARBs in an aquatic environment. This pilot study found that precipitation was directly associated with the levels of bacteria found within Shem Creek and validated that ARBs are present within local waterways in Charleston, South Carolina.